Técnicas de amostragem em empresas de auditoria na cidade do Rio de Janeiro: um estudo de casos - Andrade, Lucila Carmelia de (1988)
The objetive of this paper was to explore the existing relationship between the literature about sampling techniques and the techniques effectively utilized by auditing firms in Brazil. It sought to analyze which were the main problems found in the utilization of these techniques, and yet verify if there were differences with respect to the use of more sophisticated sampling techniques utilized by firms of national or foreign origin, and if the sizes of those firms influenced such techniques. (Chapter I). The revision of literature, had the objetive to disclose and summarize a few of the many sampling techniques which the auditing firms have at their disposal. (Chapter 11) Following, the methodology utilized in the research and the respective reason for its use were disclosed (Chapter 111) The description of the cases, realized through the questionaire in the eight auditing firms, appeared in this chapter, where each case was described individually. (Chapter IV) The results obtained were analyzed in accordance with each item of the questionaire making it possible an over alI analyzis of the sampling techniques utilized by the auditing firms in Brazil. (Chapter V) Finally, after presenting the summary and the conclusions of the research at the light of the theorical basis, ·recanrnendations and suggestions were formulated for future researches. (Chapter VI)